Comparison of pressure-swing distillation and extractive distillation with varied-diameter column in economics and dynamic control. (January 2017) - Cao, Yujuan; Hu, Jiajing; Jia, Hui; Bu, Guangle; Zhu, Zhaoyou; Wang, Yinglong
Highlights: Varied-diameter column (VDC) is used in the process design. Pressure-swing distillation and extractive distillation with VDC are compared. Dynamics is evaluated for two distillation processes using VDC. Effective control structure is explored for two distillation processes, respectively. Pressure-swing distillation with VDC has the superiority of economics and controllability. Abstract: Pressure-swing distillation and extractive distillation are two common methods for azeotrope separation. The economics and controllability are two crucial factors for evaluating the feasibility of a separation process. A varied-diameter column (VDC) was used in the process design to evaluate its economics and controllability. Five azeotropic systems were investigated in order to compare the economics of pressure-swing distillation and extractive distillation with a VDC. Results indicate that pressure-swing distillation with a VDC saves more money than extractive distillation. The dynamic control were evaluated in the acetone-methanol system for both processes with a VDC. The improved control structure for pressure-swing distillation with a VDC can handle ±20% disturbances effectively, while the improved control structure for extractive distillation with a VDC can only handle ±10% disturbances. A comparison of the two methods from the viewpoint of economics and controllability demonstrates that pressure-swing distillation is more suitable when using a VDC.